Sagot :
Answer:
omsik
Step-by-step explanation:
Addition
Positive (+) + Positive (+) = Positive (+)
Negative (-) + Negative (-) = Negative (-)
Positive (+) + Negative (-) = Subtract (With sign of greatest integer)
Negative (+) + Positive (-) = Subtract (With sign of greatest integer)
Subtraction
Positive (+) - Positive (+) = Positive (+)
Negative (-) - Negative (-) = Negative (-) + Positive (+) = Subtract (With sign of greatest integer)
Positive (+) - Negative (-) = Positive (+) + Positive (+) = Positive (+)
The subtraction of negative and positive integers becomes the addition rule of two negative integers. So, just add the two negative integers.